Study of the Philosophy of Islamic Education by KH. Ahmad Dahlan and KH. Hasyim Asyari and its Relevance to the Reform of Islamic Education - Mokmin, Mohd Waffi Albaraq Bin Mokmin; Susanto, Happy; Redho Syam, Aldo; Basri , Mokmin (JIE (Journal of Islamic Education), 2025)
This study analyses the Islamic educational thoughts of KH Ahmad Dahlan and KH Hasyim Asy'ari and their relevance to the renewal of contemporary Islamic education in Indonesia. Through a qualitative-descriptive approach based on literature study, this study examines the values, structures, and philosophical meanings of the thoughts of the two figures. The study results show that KH Ahmad Dahlan emphasised integrating religious knowledge and general knowledge in a curriculum that is adaptive to the development of the times. In contrast, KH Hasyim Asy'ari emphasised the importance of spirituality, sincerity, and character formation through Islamic boarding school education. Both agree that Islamic education must instil the values ​​of faith, knowledge, and real deeds as the foundation for forming a superior generation. This study concludes that the integration of the rational-modern thoughts of KH Ahmad Dahlan and the spiritual-conservative thoughts of KH Hasyim Asy'ari can be the basis for developing a contextual, integrative, and adaptive Islamic education model to the challenges of modernity without losing its Islamic identity. The researchers expect that this finding will provide a practical contribution to the reconstruction of the Islamic education system in Indonesia to address the persistent dualism between modernity and traditionalism.